Fostering Child Empowerment Through English Language Competency in Speaking Skills - Marudut Bernadtua Simanjuntak (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2024)
This research delves into the intricate relationship between English language competency, specifically in speaking skills, and the empowerment of young learners within the context of early childhood education. Combining descriptive qualitative research with an extensive literature review, the study elucidates the profound implications of language proficiency on child empowerment. The research employs a methodology involving in-depth interviews, systematic classroom observations, and content analysis. Subjects comprise young learners in early childhood education, with a focus on their English language proficiency in speaking. Data collection includes semi-structured interviews with educators, parents, and learners, alongside literature review findings. The outcomes reveal that language proficiency functions as a transformative tool, fostering self-confidence, self-expression, and active learning participation. Proficient speakers exhibit enhanced agency and autonomy, equipping them with cognitive tools for academic success and global navigation. Disparities in language competency and empowerment among young learners are identified, necessitating inclusive educational practices and targeted support. This research underscores educators' pivotal role, alongside engaged parents and inclusive curriculum design, in fostering language proficiency as a means of empowering children in early education. The study contributes to a holistic understanding of language's role in shaping the foundations of empowered, lifelong learners.Â